Three new species of the free-living marine nematodes from a sub-littoral station in Firemore Bay, Scotland. - Zhang, Z. (Cah. Biol. Mar., 1983)
Locality: Firemore Bay, Scotland; Cabinet:
NeMys doc_id: 17845 Locality: Firemore Bay, Scotland; Cabinet: